Analysis of the Role of Benedictus Narendra Keswara Post in Resolving Complete Systematic Land Registration (PTSL) Issues in Semarang City - Garin Dinda Azzalea (Faculty of Law, Universitas Negeri Semarang, 2025)
The Complete Systematic Land Registration (PTSL) program is one of the government’s strategic policies aimed at accelerating the legalization of land rights for the community. However, its implementation does not always run smoothly or meet expectations. In Semarang City, issues remain, such as abuse of authority by village officials on the PTSL adjudication team, and uncertainty about the program’s continuation, creating legal ambiguity for residents. This study analyzes the role of Posko BNK (Benedict Narendra Keswara), an initiative by a member of the Semarang City Regional House of Representatives (DPRD) from Dapil 2, in helping citizens resolve social and legal issues, particularly regarding PTSL. John Rawls' social justice theory, which emphasizes safeguarding the weaker members of society, is pertinent in this situation. This study uses a qualitative methodology and an empirical legal procedure. In-depth interviews, document analysis, and a study of real cases that Posko BNK handled were used to gather data. The results demonstrate that Posko BNK helps citizens who are having trouble with the PTSL process by offering advocacy, mediation, and legal assistance. This article makes it simpler for the community to report issues, get help, and get assurance that problems will be resolved. As a result, Posko BNK stands for both legislative participation and a sincere dedication to establishing social justice and legal stability for all societal levels in Semarang City.